Årsberetning - Tromsø museum. http://id.loc.gov/authorities/names/n79018533.; Universitetet i Tromsø. Institutt for museumsvirksomhet. http://id.loc.gov/authorities/names/n82041703.
Description based on: 1980. Some issues have title: Årsberetning for Mode of access: Internet. Issued by the Tromsø museum, 19 -1978; by the Universitetet i Tromsø, Institutt for museumsvirksomhet, 1979-<1981>